PENGARUH MEDIA ANIMASI TERHADAP MINAT BELAJAR DAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA SISWA KELAS V SDN 1 SUKARARA TAHUN AJARAN 2023/2024 - Hidayati, Siti; Ermiana, Ida; Rachmatul Hidayati, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The interest in learning and the learning outcomes in mathematics are still relatively low, which may be to the lack of varied learning media. This research aims to 1) determine the effect of animation media on the interest in learning mathematics; 2) determine the effect of animation media on learning outcomes in mathematics; 3) determine the effect of animation media on learning interest and learning outcomes in mathematics. This type of research is quasi experimental with a nonequivalent control group design. Data collection methods used were questionnaires, test, and observations. The analysis methods used were Manova test. Based on the results of the Test of Between-Subject Effect, the significance value for the learning interest variable, which is 0.01 < 0.05, meaning that H0 is rejected and Ha is accepted, indicating a significant effect of animation media on learning interest in mathematics for fifth-grade students at SDN 1 Sukarara. Furthermore, the results of the Test of Between-Subject Effect obtained a significance value for the learning outcomes variable, which is 0.048 < 0.05, meaning that H0 is rejected and Ha is accepted, indicating a significant effect of animation media on l earning outcomes in mathematics for fifth-grade students at SDN 1 Sukarara. Based on the results of the Manova test, a significance value of 0.000 < 0.05 was obtained, meaning that H0 is rejected and Ha is accepted, indicating a significant effect of animation media on learning interest and learning outcomes in mathematics for fifth-grade students at SDN 1 Sukarara.